2013
DOI: 10.1111/pan.12278
|View full text |Cite
|
Sign up to set email alerts
|

Caudal dexmedetomidine decreases the required concentration of levobupivacaine for caudal block in pediatric patients: a randomized trial

Abstract: Caudal dexmedetomidine reduces the MLAC values of levobupivacaine and improves postoperative analgesia in children without any neurological side effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(45 citation statements)
references
References 35 publications
3
40
0
Order By: Relevance
“…The common side effect in those receiving dexmedetomidine was bradycardia, which had been observed in four studies . There were three trials with 1 μg·kg −1 dexmedetomidine reported no cases had bradycardia .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The common side effect in those receiving dexmedetomidine was bradycardia, which had been observed in four studies . There were three trials with 1 μg·kg −1 dexmedetomidine reported no cases had bradycardia .…”
Section: Discussionmentioning
confidence: 97%
“…There were three trials with 1 μg·kg −1 dexmedetomidine reported no cases had bradycardia . Only one included trial had reported that the number of children who suffered bradycardia in CA+DEX group was more than CA group and the addition of 2 μg·kg −1 dexmedetomidine group was more than 1 μg·kg −1 group. However, no cases were reported requiring intervention in these four studies.…”
Section: Discussionmentioning
confidence: 99%
“…5,27) Caudally administered DEX was also associated with a decreased sevoflurane requirement and increased the duration of postoperative sedation in children. 12,28) The sedative and analgesic properties of The proportion of the patients who did not request oral acetaminophen was significantly higher in the DEX than in Control group (p=0.029).…”
Section: Discussionmentioning
confidence: 99%
“…Recent pediatric anesthesia examples of Dixon‐like UDM include investigating the optimal dose of propofol for pediatric tracheal intubation during sevoflurane induction , the effect of age on the dose of remifentanil for tracheal intubation , the size of a rapid bolus dose of dexmedetomidine with acceptable hemodynamic outcomes in children , MAC‐awake of sevoflurane in children , the median effective concentration of propofol during oesophagogastroduodenoscopy , the dose range of levobupivacaine or ropivacaine spinal anesthesia in neonates , the MAC of desflurane with fentanyl for laryngeal mask airway removal , the effect of epidural clonidine on MAC of levobupivacaine for caudal block , the MAC of desflurane with caudal analgesia for laryngeal mask airway removal , the optimum sevoflurane concentration for I‐gel insertion in unpremedicated children , the optimal dose of sevoflurane or desflurane for laryngeal mask airway removal in anesthetized children following cataract surgeries using subtenon block , the dose of caudal dexmedetomidine needed to decrease required concentrations of levobupivacaine for caudal block , or identifying the ropivacaine concentration required for US‐guided ilioinguinal/Iliohypogastric nerve block .…”
Section: Sequential Design Methodsmentioning
confidence: 99%